Effect of temperatures on some biological parameters of Aphis craccivora Koch (Hemiptera: Aphididae) on lentil - Muhlis Sezgin; Merve Akyıldız; Selime Olmez Bayhan; Erol Bayhan (PeerJ)
Aphis craccivora Koch (Hemiptera: Aphididae) is one of the aphid species known to cause economically important damage in lentil fields. Temperature effects on the developmental period, age stage, stage-specific survival, and reproductive capacity of A. craccivora were studied on lentil under laboratory conditions at four fixed temperatures (22.5, 25, 27.5, and 30 °C). As a result of the study, the developmental periods of nymphal stages of A. craccivora were determined as 26.04, 17.24, 23.98 and 26.74 degree days, respectively. A. craccivora had the longest pre-adult developmental period at 22.5 °C, the shortest developmental period at 27.5 °C, the highest productivity value was found as 62.74 at 25 °C, and the lowest value was found as 11.28 at 30 °C. In the study, the shortest preimaginal phases of development period, the longest individual lifespan, and the highest productivity were observed at 25 °C. In the study, the highest intrinsic rate of increase (r) of A. craccivora was 0.36 (day−1), the net reproductive rate (R0) was 63.67 (female/female), finite rate of increase (λ) was 1.43 day−1 and gross reproductive rate (GRR) was 80.88 at 25 °C. The shortest mean generation time (T) value was 8.63 days at 30 °C, while the shortest population doubling time (DT) was observed at 25 °C with 1.93 days. The most suitable temperature for population development was 25 °C for A. craccivora. The role of temperature as a key factor in determining the A. craccivora population on lentil is discussed.